Open neck injuries. Analysis of five cases. - Puig, Roberto; Boudrandi, Sonia; Bado, Alejandro (Cirugía del Uruguay, 1989)
Based on the analysis of five casses and bibliographical revision, authors insist on the indication of surgical exploratlon, thorough lesiona! inventory and primary repairing of every lesion in all cases. Authors also insist on the aggressive primary management of serious cases.